PENGARUH MEDIA EMO CARD UNTUK MEMBANTU GURU DALAM MENGELOLA EMOSI SISWA KELAS V SD NEGERI 106195 PULAU GAMBAR - Lisna Syaheni Br Saragih; Syarifa Ainun Harahap; Layil Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to determine the effect of using Emo Card media in helping teachers manage the emotions of fifth-grade students at SD Negeri 106195 Pulau Gambar. Emotional management is an important aspect of creating a conducive learning process because students' ability to recognize and regulate their emotions can influence their behavior, social interactions, and engagement during learning activities. This study employed a quantitative approach using an experimental method. The subjects of the study were fifth-grade students at SD Negeri 106195 Pulau Gambar. Data were collected through observation, questionnaires, and documentation. Emo Card was used as a learning medium to help students recognize various types of emotions, understand the causes of emotional responses, and choose appropriate responses to the emotional conditions they experience. The research data were analyzed using statistical analysis to determine changes and the effect of using Emo Card on students' emotional management abilities. The results showed that the use of Emo Card had a positive effect on students' emotional management. Students became better able to recognize, express, and regulate their emotions during the learning process. This media also helped teachers understand students' emotional conditions, allowing them to implement more appropriate classroom management strategies. Therefore, Emo Card can serve as a simple, engaging, and effective alternative medium to help elementary school teachers manage students' emotions.